LEVEL OF MOTOR ABILITIES OF CHILDREN UNTRAINED AND CHILDREN THAT WERE IN THE TRAINING PROCESS A VARIETY OF SPORTSORIENTATION (KARATE AND VOLLEYBALL) - Nela Tatar; Petar Karadžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Whit the goal to describe motorical abilities in groups of non sports and children which have some sports training activities, to calculate quantitative and qualitative difference between these groups of children in motorical abilities, it is conduct survey with the sample of 90 entities, age from 11 to 13, different sports orientation (karate and volleyball) and non sports children (scholars). In analyze, it was used system of total 15 basic - motorical variables. Also, descriptive statistical procedures were done (arithmetical means, standard deviation, coefficient of variance, minimum, maximum, skewness, Kurtosis, The Kolmogorov - Smirnov test). For quantitative difference between combination per groups in motorical abilities it was used ANOVA and MANOVA. A qualitative difference in motorical abilities was done across DISCRIMINATIVE analyses. According to quantitative and qualitative differences in motorical abilities the best performance shown group of children which train a karate.